The Effect of Implementing Deep Learning on Improving Students' Cognitive Abilities in the Independent Curriculum at Yogyakarta High Schools - Hadi, Moh. Solikul; Veri Setiawan; Putri Maulidiah Hidayah (Journal of Research in Islamic Education, 2025)
The application of artificial intelligence technology, especially Deep Learning, in the world of education is increasingly developing and has the potential to improve students' cognitive abilities. This study aims to analyze the effect of the application of Deep Learning on improving students' cognitive abilities in the Independent Curriculum in Yogyakarta High Schools. This study analyzes the effect of the application of Deep Learning technology on improving students' cognitive abilities in the Independent Curriculum in Yogyakarta High Schools. Using an interpretive quantitative method with simple linear regression, the results show a positive relationship between the application of Deep Learning and students' cognitive development with a contribution of 34.2%. The regression equation Y = 33.136 + 1.241X shows that the higher the application of Deep Learning, the higher the students' cognitive abilities. Although effective, challenges in infrastructure, teacher readiness, and student readiness still need to be overcome. With the support of the government and schools, this technology can be optimized to support more interactive, adaptive, and data analysis-based learning, thereby increasing the effectiveness of education and achieving the goals of the Independent Curriculum.